Pengaruh Keputusan Investasi, Keputusan Pendanaan,Kebijakan Dividen Dan Tingkat ProfitabilitasTerhadap Nilai Perusahaan(Studi Empiris Pada Perusahaan Non Manufaktur Yang Terdaftar Di BursaEfek Indonesia Periode 2011-2013) - Setyowati, Sulis, Dra. Nursiam, M.H., Ak., CA (2016)
The value of the company is investor perception of companies that are often associated with stock prices. High stock prices made the value of the company is also high. The share price is the price that occurs when the stock was trading in the market. The company's main objective is to maximize shareholder wealth, this can be achieved by maximizing the value of the company. But sometimes companies fail to enhance shareholder value, which is one reason the company less careful in applying the factors that affect firms value. This makes the company's performance is deemed poor by the investors.This study aimed to analyze the effect of investment decisions, financing decisions, dividend policy and the level of profitability of the enterprise value of the non-manufacturing companies listed in Indonesia Stock Exchange. The population used in this study are all non-manufacturing companies listed in Indonesia Stock Exchange during the period 2011-2013. Sampling method by purposive sampling according to criteria that have been determined. The number of samples collected as many as 51 companies (17 companies a year).The data are then analyzed by multiple regression with SPSS. The result of this study simultaneously all independent variables significantly influence the value of the company. In partial results of this study indicate that investment decisions, dividend policy and the level of profitability significantly influence the value of the company, while funding decisions has no significant effect on the value of the company.